2017
DOI: 10.24820/ark.5550190.p009.829
|View full text |Cite
|
Sign up to set email alerts
|

Self-disproportionation of enantiomers (SDE) of chiral sulfur-containing compounds via achiral chromatography

Abstract: This review presents a comprehensive, critical treatment of all the literature data related to the phenomenon of the SDE taking place during gravity-driven achiral chromatography of scalemic compounds bearing sulfoxide and thioamide functionalities. The discussion is focused on the SDE magnitude as a function of the structure iof the compound, composition of eluent and stationary phase, including some mechanistic details. An apparent possibility of application of the SDE phenomenon via achiral chromatography a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 84 publications
0
7
0
Order By: Relevance
“…In this regard, we should also mention some numerous examples of SDE via sublimation of protected, as well as zwitterionic, amino acids. 36 a While a comprehensive study in this area is clearly needed, all of the reported data clearly underscore 6 , 21 , 36 , 43 , 99 the SDE as one of the, if not the, most plausible mechanisms for the generation of prebiotic homochirality.…”
Section: Implications Of Broader Significancementioning
confidence: 99%
See 1 more Smart Citation
“…In this regard, we should also mention some numerous examples of SDE via sublimation of protected, as well as zwitterionic, amino acids. 36 a While a comprehensive study in this area is clearly needed, all of the reported data clearly underscore 6 , 21 , 36 , 43 , 99 the SDE as one of the, if not the, most plausible mechanisms for the generation of prebiotic homochirality.…”
Section: Implications Of Broader Significancementioning
confidence: 99%
“…These reviews include general accounts 3 of the SDE phenomenon as well as one general review specific for fluorine-containing compounds, 4 another dedicated to SDE via sublimation, 5 as well as several dedicated solely to the SDE via achiral chromatography. 6 Besides its scientific beauty and its profound importance for molecular chirality, the SDE has implications ranging from the origins of prebiotic homochirality to unconventional enantiopurification methods, though the risks of altering the ee unintentionally, regrettably, remain greatly unappreciated. In this report we examine the various physicochemical processes that have been reported to give rise to the SDE phenomenon as well as highlighting the pitfalls and potential advantages of the phenomenon.…”
Section: Introductionmentioning
confidence: 99%
“…This aspect is particularly important considering the rapid growth in the number of chiral, fluorine-containing pharmaceuticals [ 90 , 91 , 92 , 93 , 94 , 95 , 96 ] and agrochemicals [ 97 , 98 , 99 , 100 ]. Sulfoxides 3 , due to the highly polarized S–O bond, are another example of an SDE-phoric group [ 26 , 71 , 85 , 101 , 102 ]. Of note, prazoles, S–O containing proton pump inhibitors that reduce the amount of acid produced in the stomach, are in the top 50 most prescribed drugs currently on the pharmaceutical market.…”
Section: Preview Of the Sdementioning
confidence: 99%
“…The SDE literature has been well reviewed previously, including generally [ 5 , 47 ], for particular processes, e.g., sublimation [ 54 ] and chromatography [ 45 , 46 , 78 , 122 ], as well as for specific SDE-phoric groups, e.g., sulfoxides [ 71 , 102 ], fluorine-containing compounds [ 86 , 87 , 123 , 124 , 125 ], amides [ 102 , 126 ], and amino acids and their derivatives [ 105 ]. Of note, SDEvS has been much less reported, for the obvious reason that it is simply a less utilized technique compared to chromatography for routine purification.…”
Section: Pedagogic Examples From the Literaturementioning
confidence: 99%
“…In spite of the SDE being well‐documented and a large number of examples being described in several fine reviews on the phenomenon involving processes other than recrystallization, nevertheless, it remains that the SDE phenomenon is not widely appreciated by researchers, at least for processes other than recrystallization. The reviews on the SDE phenomenon include general accounts of the SDE phenomenon, as well as one general review specific for fluorine‐containing compounds , another dedicated to SDE via sublimation , as well as several dedicated solely to the SDE via achiral chromatography . Here in this commentary, the focus is on chromatographic techniques, especially with regards to, those techniques of wide application and interest for the readership of Electrophoresis .…”
Section: Mplc Versus Gravity‐driven Column Chromatography For N‐acetymentioning
confidence: 99%